Astrocyte Elevated Gene-1 Mediates Glycolysis and Tumorigenesis in Colorectal Carcinoma Cells via AMPK Signaling - Hong-tao Song; Yu Qin; Guo-dong Yao; Zhen-nan Tian; Song-bin Fu; Jing-shu Geng (Mediators of Inflammation, 2014)
To investigate the role of AEG-1 in glycolysis and tumorigenesis, we construct myc-AEG-1 expression vector and demonstrate a novel mechanism that AEG-1 may increase the activity of AMPK by Thr172 phosphorylation. The higher expression levels of AEG-1 in colorectal carcinoma cells were found but showed significant difference in different cell lines. To study the role of AEG-1 in colorectal cells, myc-AEG-1 vector was constructed and transfected into NCM460 colonic epithelial cells. We observed consistent increasing of glucose consumption and lactate production, typical features of anaerobic glycolysis, suggesting that AEG-1 may promote anaerobic glycolysis. Moreover, we noted that AMPK phosphorylation at Thr172 as well as pPFK2 (Ser466) was increased in NCM460 cells overexpressing AEG-1. Compound C may block AMPK and PFK2 phosphorylation in both control and AEG-1-overexpressed cells and decrease the glucose consumption and lactate production. The present findings indicated that reduced AEG-1 protein levels by RNAi may decrease the glucose consumption and lactate production in HCT116 colorectal carcinoma cells. The present identified AEG-1/AMPK/PFK2 glycolysis cascade may be essential to cell proliferation and tumor growth. The present results may provide us with a mechanistic insight into novel targets controlled by AEG-1, and the components in the AEG-1/AMPK/PFK2 glycolysis process may be targeted for the clinical treatment of cancer.